Analisis Sidik Lintas Beberapa Karakter Komponen Hasil Terhadap Daya Hasil Padi Sawah Pada Aplikasi Agrisimba - WAGE R. ROHAENI; KARSIDI PERMADI (Fakultas Pertanian Universitas Udayana, 2012)
Pathway analysis is the further test after correlation test. Correlation between characters of plantwill be change in one field condition to other condition field. Correlation between characters on organicor semi-organic farming system still studied limitedly included in our project about organic/semi-organicfarming. Agrisimba is the probiotic microbes, one of technology for decomposing straw rapidly. Thestudy was done on November 2011 – March 2012 in Sawah Kidul Village, Pasawahan – PurwakartaDistrict with “farmer participatory on farm research method”. Inpari 13 was the indicator variety andAgrisimba was the treatment to decomposing straw rapidly in rice field to support organic farmingsystem as this topic study. Correlation analysis showed that plant high and value of pithy grain/tasselhave level of closeness significantly with yield character. On further test analysis showed that plant highwas the highest value of direct influence and 100 grain weight was highest value of indirect influence foryield character.